Patterns and Mechanisms of Legume Responses to Nitrogen Enrichment: A Global Meta-Analysis - Juan Tang; Wei Li; Ting Wei; Ruilong Huang; Zhuanfei Zeng (Plants)
Nitrogen (N), while the most abundant element in the atmosphere, is an essential soil nutrient that limits plant growth. Leguminous plants naturally possess the ability to fix atmospheric nitrogen through symbiotic relationships with rhizobia in their root nodules. However, the widespread use of synthetic N fertilizers in modern agriculture has led to N enrichment in soils, causing complex and profound effects on legumes. Amid ongoing debates about how leguminous plants respond to N enrichment, the present study compiles 2174 data points from 162 peer-reviewed articles to analyze the impacts and underlying mechanisms of N enrichment on legumes. The findings reveal that N enrichment significantly increases total legume biomass by 30.9% and N content in plant tissues by 13.2% globally. However, N enrichment also leads to notable reductions, including a 5.8% decrease in root-to-shoot ratio, a 21.2% decline in nodule number, a 29.3% reduction in nodule weight, and a 27.1% decrease in the percentage of plant N derived from N2 fixation (%Ndfa). Legume growth traits and N2-fixing capability in response to N enrichment are primarily regulated by climatic factors, such as mean annual temperature (MAT) and mean annual precipitation (MAP), as well as the aridity index (AI) and N fertilizer application rates. Correlation analyses show that plant biomass is positively correlated with MAT, and tissue N content also exhibits a positive correlation with MAT. In contrast, nodule numbers and tissue N content are negatively correlated with N fertilizer application rates, whereas %Ndfa shows a positive correlation with AI and MAP. Under low N addition, the increase in total biomass in response to N enrichment is twice as large as that observed under high N addition. Furthermore, regions at lower elevations with abundant hydrothermal resources are especially favorable for total biomass accumulation, indicating that the responses of legumes to N enrichment are habitat-specific. These results provide scientific evidence for the mechanisms underlying legume responses to N enrichment and offer valuable insights and theoretical references for the conservation and management of legumes in the context of global climate change.